Bolus transit and airway protection coordination in older dysphagic patients - Kendall, K A; Leonard, R J (The Laryngoscope, 2001)
The intent of this study was to identify and characterize abnormalities of bolus pharyngeal transit and airway protection in a group of elderly patients with dysphagia. A retrospective analysis of dynamic videofluoroscopic swallowing studies performed in patients over the age of 65 was carried out. The study was limited to individuals with no obvious medical or surgical cause of dysphagia. Pharyngeal bolus transit times were determined and compared with those from 60 young normal control subjects and 23 elderly control subjects. The timing of airway closure was analyzed in terms of bolus position in the pharynx. Prolonged bolus transit times were identified in 61% of patients investigated and 65% of elderly control subjects. Overall, the onset of airway closure was appropriate for the position of the bolus in the pharynx but was slow to achieve completion. Elderly control subjects were found to elevate the larynx early in the swallow. Delayed airway closure was identified as a contributor to aspiration in some dysphagic subjects. Pharyngeal transit of the bolus may be prolonged in elderly individuals. Swallowing coordination mechanisms appear to be intact in the majority of elderly patients with dysphagia, but gestures may be weak and ineffective. Early laryngeal elevation may be an effective strategy to avoid aspiration.